2007
DOI: 10.1097/hjh.0b013e328136bd21
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol as initial antihypertensive therapy: an observational study comparing first-line agents

Abstract: The low event rates for all cohorts suggest that atenolol has not been associated with a significant burden of cardiovascular morbidity or mortality in its traditional role for uncomplicated hypertension. Further study is needed to identify the specific types of patients that should avoid atenolol as an antihypertensive agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 17 publications
0
16
0
2
Order By: Relevance
“…The lowest days supply quantity allowed was 1 month. Previously, we have similarly tested the reliability of the fillfrequency measure using statin medications and have found a high correlation (rϾ0.9) to the estimated PDC that is reproducible in datasets of hypertensive 9 and post-myocardial infarction 15 subjects in Saskatchewan.…”
Section: Adherence Measurementioning
confidence: 99%
See 1 more Smart Citation
“…The lowest days supply quantity allowed was 1 month. Previously, we have similarly tested the reliability of the fillfrequency measure using statin medications and have found a high correlation (rϾ0.9) to the estimated PDC that is reproducible in datasets of hypertensive 9 and post-myocardial infarction 15 subjects in Saskatchewan.…”
Section: Adherence Measurementioning
confidence: 99%
“…These Saskatchewan Health databases have been used in numerous pharmaco-epidemiological studies, and are considered to be both comprehensive and of high quality. 8,9 Study Population…”
Section: Data Sourcementioning
confidence: 99%
“…A cohort study from the province of Saskatchewan, Canada, found similar frequency of death from any cause, stroke or transient ischemic attack, myocardial infarction, and unstable angina among users of atenolol (2.3%), ACEIs (3.6%), hydrochlorothiazide (2.9%), and calcium antagonists (3.9%), while atenolol was not associated with difference in risk compared to other drugs after adjustment by covariates. 22 A study including women aged 50 years or older reported that there was a slight increase of risk for patients taking CCBs compared with TDs; however, this became nonsignificant after adjustment for risk factors and exclusion of women with diabetes mellitus. There were no significant differences in coronary disease events and strokes between patients taking ACEIs or diuretics.…”
mentioning
confidence: 99%
“…Эти результаты согласуются с данными проспективного исследования диабета UKPDS (United Kingdom Prospective Diabetes Study) [426] . Эти результаты совпадают также с резуль-татами крупного наблюдательного исследования, использую-щего различные режимы антигипертензивной терапии в тече-ние более длительного периода, чем в рандомизированных испытаниях, и в которых частота сердечно-сосудистых небла-гоприятных исходов при терапии на основе атенолола была не выше, чем на фоне других антигипертензивных препаратов [405] .…”
Section: антигипертензивные препаратыunclassified